Introduction to Special Issue: Placemaking Beyond Cities. : Geomedia perspectives on everyday life in small towns and rural communities - Braunerhielm, Lotta; Grip, Lena; Ljungberg, Emilia; Ryan Bengtsson, Linda (Culture Unbound, 2024)
This special issue of Culture Unbound directs attention beyond cities, to small towns and rural communities, and the practices taking place there. Referring to a previous special issue on ‘Rural Media Spaces’ from 2010, this special issue revisits the notion of ‘the rural’ versus ‘the urban’ through the concept of placemaking and geomedia. In a mediatized society, placemaking practices cannot be understood without simultaneously understanding different media practices and how they affect place. A geomedia perspective on placemaking beyond cities, therefore, brings new perspectives on media representations of small towns and rural communities, related to the materialization of space and how we engage with and perceive the world. Geomedia also includes a focus on layers of digitalization and new media in the relations between place and practice. The issue brings together researchers from a wide range of subjects, and the articles in this volume address empirical examples from different rural places and small towns in Sweden and internationally. Taken together, a manifold of issues relating to media and placemaking beyond cities are covered, for example, inclusion/exclusion, representation, resistance, community building, belonging, and identification.